A specialization that comes from specialty: bringing closer magazine and specialized journalism in Vida Simples - Tavares, Frederico De Mello Brandão (Brazilian journalism research, 2011)
This paper discusses the processes that involve the creation of a specialized magazine concerned with a major theme, reflecting on how, based on this context, it is possible to attain the form of a type of specialized journalism. It starts from an analysis of the editorials (“letters to the readers”) of Vida Simples (Simple Life), a monthly published by Editora Abril, noting how the magazine, when speaking of itself, allows the perception of its specific characteristics that compose its editorial identity and characterize the “form” of its journalism, its way of “being a magazine”. At the end of the text, there is the observation of how the issue of the quality of life - the central focus of the publication – by incorporating the journalistic logic of the magazine and at the same time being incorporated by it, makes it take on the appearance of a specialty which is consequently reflected in its specialization.